Enhanced multi-factor authentication for web - Morais, David Gomes (2023)
With the recent growth of Internet of Things (IoT), cloud platforms and, consequently, the exponential increase in online exchanges encompassing sensitive information pertinent to users, it has become necessary to implement strong authentication methods to minimize the risk of user impersonation. The aim of this work is to enhance the protection of private information, by developing a prototype which employs risk assessment aligned with a Multi-Factor Authentication (MFA) system, in a platform that can be easily integrated in applications in order to delegate the authentication process to an external platform. While pushing forward the flexibility and supportability of multiple browsers and client applications, the main goal of the solution is to protect against user impersonation and illegitimate access to user accounts, while keeping the intrinsic protection of MFA systems and rendering social engineering attacks inconsequential with the aid or risk-based adaptability.